Evaluation of bacterial contamination on irreversible hydrocolloid impressions before and after disinfection - Lais Falcão Borgo; Francisco de Assis Bozzetti; Julieti Fernandes Flor; Paula Sampaio de Mello; Thaís Dias Lemos Kaiser (Associação Brasileira de Odontologia, 2018)
Objective: to evaluate microbial contamination and characterization of irreversible hydrocolloid impressions, as well as the antimicrobial efficacy of 1% sodium hypochlorite and 2% chlorhexidine solutions in decontamination for 5 and 10 minutes. Material and Methods: we made upper arch impressions from 50 dentistry students of the Escola Superior São Francisco de Assis, the sample from each impression was collected with a sterile cotton swab and inoculated in BHI broth, being transferred to solid blood agar for evaluation of the contamination. Subsequently, the impressions were washed or disinfected with 1% hypochlorite or 2% chlorhexidine, a new collection was made to evaluate the degree of decontamination by spraying. Results: data regarding the number of CFU before and after the decontamination procedures were tabulated, we compared the results using the Wilcoxon signed rank test. Thus, we verified that the microbial load was not reduced after washing the impression with sterile water. In contrast, decontamination using both chemical agents proved to be effective, for 5 and 10 minutes. Moreover, from the characterization of the microorganism test, we noticed that most bacteria are common within the oral microbiota. However, we also found Staphylococcus aureus in 5 impressions (8.33%), a pathogenic bacterium that is not common in the oral microbiota. Conclusion: decontamination procedures are effective to remove microorganisms present in impressions.